2021
DOI: 10.3390/molecules26041105
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Equol (Soy Metabolite) on Breast Cancer

Abstract: Equol is a soy isoflavone metabolite that can be produced by intestinal bacteria. It is lipophilic and resembles natural oestrogens with an affinity to oestrogen receptors. This review is focused on how equol affects breast cancer, as evidenced by in vivo and in vitro studies. Equol is considered chemoprotective in specific endocrine-related pathologies, such as breast cancer, prostate cancer, cardiovascular diseases, and menopausal symptoms. In humans, not everyone can produce equol from gut metabolism. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…This could influence the global results of studies. Overall, it seems that S -equol has more anticancer than oncogenic effects, although future studies should specify the required concentration of 9 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could influence the global results of studies. Overall, it seems that S -equol has more anticancer than oncogenic effects, although future studies should specify the required concentration of 9 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gercel-Taylor, et al [ 83 ] demonstrated an inhibitory effect of genistein on ovarian cancer cell growth, and daidzein is effective in inhibiting the proliferation of lung cancer both in vitro and in vivo [ 84 ]. Additionally, the presence of equol and O -DMA has been associated with the inhibition of cancer cell proliferation and a chemoprotective role in the prevention of several cancers [ 85 , 86 , 87 ].…”
Section: Effects Of the Isoflavones Metabolism By Labmentioning
confidence: 99%
“…It can regulate cellular pathways, such as inhibition of matrix metalloproteins that abrogates metastasis and increases demethylation of BRCA1 and BRCA2 87 . S‐equol has also been reported to alter the activity of breast cancer resistance proteins, cell proliferation, and apoptosis 88 . Furthermore, free fatty acids (FFA) of varied chain lengths are produced by gut microbiota.…”
Section: Influence Of Gut Microbiome Composition On Incidence and Pro...mentioning
confidence: 99%
“… 87 S‐equol has also been reported to alter the activity of breast cancer resistance proteins, cell proliferation, and apoptosis. 88 Furthermore, free fatty acids (FFA) of varied chain lengths are produced by gut microbiota. The activation of FFA receptor 2 (FFAR2) by short chain fatty acids leads to elevated levels of E‐cadherin in mesenchymal cells that indicates the potential of this metabolite in mesenchymal‐to‐epithelial transition, thereby decreasing metastasis.…”
Section: Influence Of Gut Microbiome Composition On Incidence and Pro...mentioning
confidence: 99%